Evaluating the sterility of orthodontic materials as received from the manufacturer and that exposed to clinic environment - in vitro study - Musaddique, Shafi Sayyed; Ajit, Kalia; Ashwith, Hegde; Nasim, Mirdehghan; Faraaz Mohamed, Ali Khan (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Introduction: Sterilization in orthodontics has been discussed and stressed over times in the dental literature. Sterility of orthodonticmaterials should be of prime interest to the orthodontist as a health care professional and he should take appropriate measures toprevent the risk of cross infection. Aim: To evaluate the sterility of orthodontic materials as received from the manufacturer and that exposed to clinic environment for 6 months. Materials and methods: The sterility of orthodontic materials "as received" from the manufacturer and "clinically exposed" (unused materialsstored in the clinic environment for a period of 6 months) was microbiologically evaluated (universal & conventional PCR). The materialswhich were included in this study were the sealed and unsealed orthodontic archwires, molar bands, elastomeric module, stainless steelbracket, coil spring and tungsten carbide burs of various brands (American Orthodontics, 3M Unitek, Ormco, Orthosystems, G&H,Modern Orthodontics, SS white etc). Results: After universal and conventional PCR, the detection of micro-organisms in all materials was significantly higher in the clinicallyexposed samples compared to as received samples from manufacturers (P <0.001). The detection of micro-organisms in all orthodonticwires is significantly higher in the unsealed samples compared to sealed samples (P <0.001). In universal PCR, the detection of microorganismsin all materials (Coil spring, E-chain, Elastomeric, Molar brands, Tungsten carbide) except for SS brackets is significantly higherin both as received and clinically exposed samples. Conclusion: After universal and conventional PCR, we conclude that bacteria were present on almost all orthodontic materials "as receivedfrom the manufacturers" and that exposed to a clinical environment. Therefore all materials should be sterilized before use in patients.